Combined effect of oxidative stress-related gene polymorphisms on atherosclerosis - Katakami, N.; Sakamoto, K.; Kaneto, H.; Matsuhisa, M.; Shimizu, I.; Ishibashi, F.; Osonoi, T.; Kashiwagi, A.; Kawamori, R.; Hori, M.; Yamasaki, Y. (Biochemical and Biophysical Research Communications, 2009)
It is well known that oxidative stress plays critical roles in the pathogenesis of atherosclerosis. In this study, we enrolled 1746 type 2 diabetic subjects, determined 4 common genetic variants related to oxidative stress ( glutamate-cysteine ligase modifier subunit (GCLM) C-588T, myeloperoxidase G-463A, human paraoxonase 1 Gln192Arg and NAD(P)H oxidase p22phox C242T polymorphisms), and measured carotid intima-media thickness (IMT) as a surrogate marker for atherosclerosis. GCLM C-588T polymorphism was associated with average IMT (AveIMT) ( r = 0.090, p = 0.0008), but the association between the other 3 polymorphisms and AveIMT did not reach the statistical significance. However, AveIMT was significantly greater as the total number of 4 concomitant “pro-oxidant alleles” in each subject was increased ( r = 0.108, p < 0.0001). Furthermore, the number of “pro-oxidant alleles” was a risk factor for a high AveIMT independently of conventional risk factors ( p = 0.0003). In conclusion, accumulation of oxidative stress-associated alleles was associated with carotid atherosclerosis in type 2 diabetic patients.